Unlocking the Impact of Chemicals on the Health and Safety of Pharmaceutical Workers: A Concise Review - Otitolaiye, Victor Olabode; Al-Naaimi, Maryam; Rasha Abdelrahim, (International Journal of Occupational Safety and Health, 2024)
The paper presents a concise review of the historical development of the pharmaceutical industry and the problems related to chemical exposure on the health and safety of employees. The industry has greatly improved healthcare worldwide, but it is one of the riskiest due to problems like exposure to dangerous chemicals. Herein, we provide evidence of the health repercussions of pharmaceutical exposure. The paper notes that a diversified approach is required to address these issues. Firstly, there is a need to extensively examine and understand the degree of chemical exposure and its long-term health implications. Tighter laws are necessary to implement higher environmental and safety standards, whereas employee education and training will help to raise awareness of possible hazards. Green chemistry and sustainable methods will curb or mitigate the use of hazardous chemicals and waste generation. Moreover, there is a need to promote sustainable and safer work cultures through safer behaviours, increased public awareness, and community interaction. Pharmaceutical companies must commit to continuous enhancement of their operations, decrease the risks associated with chemical exposure, and put worker and environmental health first. This strategy contributes to a safer and more sustainable pharmaceutical future by being in line with the industry’s commitment to innovation and safety.